1995
DOI: 10.1002/j.1556-6676.1995.tb01757.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Roles and Self‐Esteem: A Consideration of Environmental Factors

Abstract: Much empirical research has examined the psychological well‐being of individuals with varying gender role orientations. This research has typically shown masculinity to be a strong correlate of self‐esteem and femininity to be relatively unrelated to self‐esteem. This research has often failed to consider the relative environmental influences impacting this process. This study examines the relationships of masculinity and femininity to self‐esteem and environmental presses for each of these sets of behavioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 24 publications
0
26
1
1
Order By: Relevance
“…Instead of perceiving these traits as positive and adaptive, as studies have shown them to be (Burnett et al, 1995;Whitley, 1985), society has labeled them as atypical and problematic for women. Thus, it is not surprising that some girls are unhappy with traits society deems to be masculine and desire to be more of what society considers to be feminine.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Instead of perceiving these traits as positive and adaptive, as studies have shown them to be (Burnett et al, 1995;Whitley, 1985), society has labeled them as atypical and problematic for women. Thus, it is not surprising that some girls are unhappy with traits society deems to be masculine and desire to be more of what society considers to be feminine.…”
Section: Discussionmentioning
confidence: 94%
“…Because self-esteem is positively related to standardized measures of masculinity in both male and female adolescents (Adams & Sherer, 1985;Burnett, Anderson, & Heppner, 1995;Long, 1989;Marsh, Antill, & Cunningham, 1987;Ruble & Martin, 2000;Whitley, 1985), it is highly likely that self-esteem mediates the relationship between father's absence and gender role development. This may be particularly true for adolescent boys because their perceptions of masculinity are so intertwined with their self-esteem (Berrenberg & Deyle, 1989;Burnett et al, 1995;Long, 1989;Whitley, 1985). Therefore, we also examined the effects of selfesteem on gender role development in the current study.…”
Section: Conceptual and Methodological Issuesmentioning
confidence: 97%
“…7 To that end we included measures of gendered items from the Personal Attributes Questionnaire created by Spence and Helmreich (1978) and our selection was informed by the recent publication by Ward et al (2006), which reduced the number of questions and improved the internal consistency of the scales. Ward et al (2006) note that the scales of the Personal Attributes Questionnaire have been applied to assess masculinity and femininity in gender role and gender differences research (Burnett et al , 1995;Celluci et al , 1998;Dade & Sloan, 2000;Toller et al , 2004) to measure the concepts of agency and communion (Abele, 2003;Fritz, 2000;Fritz & Helgeson, 1998;Helgeson, 1994) or as a measure of instrumental or expressive traits (Cox et al , 2004;Spence, 1993;Spence & Buckner, 1995). Ward et al renamed the factors of the revised scale "agency" (using the masculine measures), and "communion" (using the feminine measures), terms first used by Bakan (1966).…”
Section: Agency and Communionmentioning
confidence: 99%
“…Most societies that emphasize success and achievement place a high value on instrumental characteristics (Wolfram et al 2009). So, it could be assumed that those individuals who have these traits perhaps receive more respect from others and hence evaluate themselves more positively than individuals who display fewer of these instrumental traits in both western and eastern cultures (Burnett et al 1995;Kim and Choi 2007;Wolfram et al 2009). Thus, this body of research indicated that instrumentality was positively associated with some positive aspects of psychological well-being (e.g., self-esteem) using samples from the U.S. (Sharpe et al 1995;Wang et al 1997;Whitley 1983Whitley , 1984 and from Korea (Kim and Choi 2007) and negatively to some negative aspects of psychological adjustment (e.g., depression) from the U.S. (Sharpe and Heppner 1991;Whitley 1983, Whitley 1984, Korea (Choi et al 2005), and Germany (Wolfram et al 2009).…”
Section: Introductionmentioning
confidence: 98%